Molecular profiling demonstrates modulation of immune cell function and matrix remodeling during luteal rescue†. Issue 6 (27th March 2019) - Hughes, Camilla K; Maalouf, Samar W; Liu, Wan-Sheng; Pate, Joy L
Abstract: The corpus luteum (CL) is essential for maintenance of pregnancy in all mammals and luteal rescue, which occurs around day 16–19 in the cow, is necessary to maintain luteal progesterone production. Transcriptomic and proteomic profiling were performed to compare the day 17 bovine CL of the estrous cycle and pregnancy. Among mRNA and proteins measured, 140 differentially abundant mRNA and 24 differentially abundant proteins were identified. Pathway analysis was performed using four programs. Modulated pathways included T cell receptor signaling, vascular stability, cytokine signaling, and extracellular matrix remodeling. Two mRNA that were less in pregnancy were regulated by prostaglandin F2A in culture, while two mRNA that were greater in pregnancy were regulated by interferon tau. To identify mRNA that could be critical regulators of luteal fate, the mRNA that were differentially abundant during early pregnancy were compared to mRNA that were differentially abundant during luteal regression. Eight mRNA were common to both datasets, including mRNA related to regulation of steroidogenesis and gene transcription. A subset of differentially abundant mRNA and proteins, including those associated with extracellular matrix functions, were predicted targets of differentially abundant microRNA (miRNA). Integration of miRNA and protein data, using miRPath, revealed pathways such as extracellular matrix–receptor interactions, abundance of glutathione, and cellular metabolism and energy balance. Overall, this study has provided a comprehensive profile of molecular changes in the corpus luteum during maternal recognition of pregnancy and has indicated that some of these functions may be miRNA-regulated. Abstract : Transcriptomic and proteomic profiling demonstrated that luteal rescue during early pregnancy is mediated by a variety of events, including alteration of immune cell function and matrix remodeling, and that these may be miRNA-regulated.